Microindentation Technique to Create Localized Cartilage Microfractures. Issue 10 (20th October 2021) - Chawla, Dipul; Han, Guebum; Eriten, Melih; Henak, Corinne R.
Abstract: Articular cartilage is a multiphasic, anisotropic, and heterogeneous material. Although cartilage possesses excellent mechanical and biological properties, it can undergo mechanical damage, resulting in osteoarthritis. Thus, it is important to understand the microscale failure behavior of cartilage in both basic science and clinical contexts. Determining cartilage failure behavior and mechanisms provides insight for improving treatment strategies to delay osteoarthritis initiation or progression and can also enhance the value of cartilage as bioinspiration for material fabrication. To investigate microscale failure behavior, we developed a protocol to initiate fractures by applying a microindentation technique using a well‐defined tip geometry that creates localized cracks across a range of loading rates. The protocol includes extracting the tissue from the joint, preparing samples, and microfracture. Various aspects of the experiment, such as loading profile and solvent, can be adjusted to mimic physiological or pathological conditions and thereby further clarify phenomena underlying articular cartilage failure. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Harvesting and dissection of the joint surfaces Basic Protocol 2 : Preparation of samples for microindentation and fatigue testing Basic Protocol 3 : Microfracture using microindentation Basic Protocol 4 : Crack propagation under cyclic loading